PENGARUH BRAND IMAGE, BRAND TRUST DAN PERCEIVED VALUE TERHADAP BRAND LOYALTY PADA PELANGGAN KLINIK KECANTIKAN NANISA BEAUTY AND DENTAL CLINIC DI KOTA SIDOARJO - Mucharoro, Hanim (Jurnal Ilmiah Mahasiswa FEB, 2017)
The role of the Brand is one of the important factor in marketing activities by offering products and services. Brand is not just something that can display the value of its current status, but can also provide a specific value in the hearts or minds of the customer. The purpose of this research was to analyze the effect of brand image, brand trust, and perceived value againts brand loyalty on customer clinics beauty Nanisa Beauty and Dental Clinic in the town of Sidoarjo. This research uses 140 samples with non-probability sampling methods with purposive sampling technique. Methods of data analysis used was multiple linear regression analysis using SPSS 20.00 for windows.The result showed that the brand image of variable (X1) influential variables significantly to brand loyalty (Y) with significant value i.e 0,075. Brand trust (X2) influential variables significantly to brand loyalty (Y) with significantly to brand loyalty (Y)Â  with significant value i.e 0,000 and preceived value (X3) significant influential variable againts brand loyalty (Y) with significant value i.e 0,011.Keywords: brand image, brand trust, perceived value, brand loyalty